2014
DOI: 10.1021/am501398s
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation and Mechanism for Enhanced Electron Emission in Hydrogen Plasma-Treated Diamond Nanowire Films

Abstract: The effect of hydrogen plasma treatment on the electrical conductivity and electron field emission (EFE) properties for diamond nanowire (DNW) films were systematically investigated. The DNW films were deposited on silicon substrate by N2-based microwave plasma-enhanced chemical vapor deposition process. Transmission electron microscopy depicted that DNW films mainly consist of wirelike diamond nanocrystals encased in a nanographitic sheath, which formed conduction channels for efficient electron transport and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 62 publications
(77 reference statements)
1
22
0
Order By: Relevance
“…7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties. However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties. However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies. In spite of high turn-on¯eld of bare SiNWs, availability of wide spectrum of synthesis procedure, [17][18][19][20][21][22] comparatively more dense emitting tips and above all compatibility in semiconducting vacuum microelectronic systems 8,28 make SiNWs°exible in electronics and optoelectronics device fabrication. The¯eld emission properties of SiNWs such as turn-on¯eld, emitting current density per unit area and¯eld enhancement factor can be signi¯cantly improved by functionalized coating of ultra-nanocrystalline diamond, 13,29 carbon nanotubes, 30 and various metallic thin¯lms 31 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Panda et al 99 produced diamond nanowires by Hplasma etching of nitrogen-containing diamond films generated by a MW-CVD process. The H-plasma treatments produced wire-like diamond nanocrystals encased in a nanographitic sheet (Fig.…”
Section: D Structuresmentioning
confidence: 99%
“…However, the disadvantages of hydrogen plasma treatment are also obvious. It can cause remarkable etching of sp 2 ‐bonded carbon and the deposition of a non‐diamond hydrocarbon layer on the surface during the cooling‐down process . To overcome the above drawbacks, Suffredini et al reported that H‐termination of of boron‐doped diamond (BDD) films could be easily achieved by electrochemical pretreatment.…”
Section: Introductionmentioning
confidence: 99%